Acupressure At Pericardium Point 6 On The Reduction Of Nausea And Vomiting In Pregnant Women In Trimester 1 At Puskesmas Oesapa - Lius, Selviana Ona; Kapitan, Meiyeriance; Kleden, Simon Sani (Jurnal EduHealth, 2024)
During the first trimester most pregnant women experience excessive nausea and vomiting. Therapy to reduce excessive nausea and vomiting in first trimester pregnant women is acupressure therapy at pericardium point 6. The purpose of this study was to determine the action of acupressure at pericardium point 6 on reducing excessive nausea and vomiting in first trimester pregnant women at the Oesapa health center. This study used a qualitative approach with a type of case study research with a descriptive research design. The results of the study, before acupressure action was taken, nausea vomiting in Mrs. M was severe nausea vomiting (18), and Mrs. D was severe nausea vomiting (20). After acupressure for 3 days, the results decreased, in Mrs. M became moderate nausea and vomiting (15), in Mrs. D became moderate nausea and vomiting (16). In conclusion, acupressure action at pericardium point 6 can reduce excessive nausea and vomiting in first trimester pregnant women. It is hoped that patients and families can apply acupressure therapy to reduce excessive nausea and vomiting in first trimester pregnant women.